Cyber Risk: Too Big to Insure? Risk Transfer Options for a mercurial risk class - Martin Eling; Jan Hendrik Wirfs (Verlag Institut für Versicherungswirtschaft der Universität St. Gallen, 2016)
This study is the first systematic discussion of potential risk transfer options for cyber risks. We compare several risk transfer options, including insurance, reinsurance and alternative risk transfer. Moreover, we discuss the potential role of the government and the capacity of insurance pools to improve insurability. On the methodological side, we rely on both qualitative and quantitative analyses to justify our conclusions. We use Berliner's insurability framework and expected utility analysis of different cyber specific scenarios. We then compare our theoretical findings with the opinions of market participants in an empirical study.
Keywords: 360; IT-Kriminalität; Erwartungsnutzen; Versicherungsbeitrag; Risikomodell; Theorie